2005
DOI: 10.1021/ja0500254
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Organocatalysts for Enantioselective aza-Morita−Baylis−Hillman Reaction

Abstract: The efficient and novel bifunctional organocatalyst for the enantioselective aza-Morita-Baylis-Hillman (aza-MBH) reaction has been established with (S)-3-(N-isopropyl-N-3-pyridinylaminomethyl)BINOL for the first time. The reaction proved to be deeply influenced by the position of the Lewis base attached to BINOL. The acid-base-mediated functionalities for the activation of the substrate and the fixing of conformation of the organocatalyst are harmoniously performed to promote the reaction with high enantiocont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(61 citation statements)
references
References 27 publications
3
56
0
2
Order By: Relevance
“…12 Using a specifically designed ionic liquid with a chiral anion, enantioselectivities of up to 84% ee were obtained in the aza-Baylis-Hillman reaction. These results are comparable with the values obtained with the best catalysts for the enantioselective aza-Baylis-Hillman reaction in conventional solvents (94% ee, 13 83% ee 14 ). These results indicate that the key to effective chirality transfer lies in strong intermolecular interactions such as electrostatic attraction and hydrogen bonding between the solvent molecules and the intermediates or the transition states of the enantioselective reaction step.…”
Section: Introductionsupporting
confidence: 87%
“…12 Using a specifically designed ionic liquid with a chiral anion, enantioselectivities of up to 84% ee were obtained in the aza-Baylis-Hillman reaction. These results are comparable with the values obtained with the best catalysts for the enantioselective aza-Baylis-Hillman reaction in conventional solvents (94% ee, 13 83% ee 14 ). These results indicate that the key to effective chirality transfer lies in strong intermolecular interactions such as electrostatic attraction and hydrogen bonding between the solvent molecules and the intermediates or the transition states of the enantioselective reaction step.…”
Section: Introductionsupporting
confidence: 87%
“…Sasai et al reported an aza-Morita-Baylis-Hillman reaction catalyzed by the bifunctional organocatalyst 16 (Scheme 29). [50] The pyridyl moiety plays as the role of a Lewis base unit and the diol moiety acts as a Brønsted acid site. [51] Interestingly, only the 3-pyridylaminomethyl moiety at the 3-position turned out to be quite effective with respect to both enantioselectivity and reactivity.…”
Section: Binol Derivativesmentioning
confidence: 99%
“…Recently, hydrogen-bond donors such as ureas/thioureas, [10][11][12][13][14][15][16][17][18][19][20][21][22][23] BINOL/diols, [24][25][26][27][28][29][30][31][32] and phosphoric acids [33][34][35][36][37][38][39][40] have been also recognized as efficient organocatalysts. Novel urea and thiourea derivatives were developed as organocatalysts and their potential as a general acid has been successfully demonstrated by several groups.…”
Section: Introductionmentioning
confidence: 99%